Determining the Efficiency of Direct Medical Services Affiliated with Iranian Social Security Organization using Stochastic Frontier Analysis (SFA) Method in 2008-2015 - fatemeh esmaili; mohammadhosein Mehrolhassani; reza goudarzi; mohsen Barouni (Tehran University of Medical Sciences, 2019)
Background: Considering the increasing growth in health care costs along with the resources finitude; therefore, improving the efficiency and efficient use of resources is considered as one of the main priorities of the health system. The aim of this study was to determine the efficiency of direct medical services affiliated with Iranian Social Security Organization using Stochastic Frontier Analysis (SFA) Method in 2008-2015.   Materials & Methods: In this descriptive- analytical study, performance of 30 units of direct medical services affiliated with Iranian Social Security Organization was analyzed using Stochastic Frontier Analysis (SFA) Method. The number of active beds, physicians, nurses and staff were used as inputs and combined variables obtained from factor analysis were selected as output. Frontier version 4.1 was used to determine the efficiency and Stata version 14 was used to study the effective factors on efficiency.   Results: The average technical efficiency of studied units was 0.816. Based on the value of index of likelihood ratio test ( LR = 100.45 ), Cobb-Douglas production function was selected as the best model.   Conclusion: Based on the findings of this study, adjusting surplus manpower, congenital planning for increasing efficiency and resource management should be the priority of the managers so that they can increase the level of efficiency of studied units and reduce the costs to the least possible.